LEUIT AND CUSTOMARY VIOLATION IN BADUY (Case Study of Leuit Fire in Cisaban Baduy Village) - Yulia, Rena; Prakarsa, Aliyth; Fauzi, Ahmad (Faculty of Law, Universitas Jenderal Soedirman, 2018)
May 23, 2017, Kampung Cisaban Baduy Luar burned down. A total of 84 houses of Baduy residents and 200 leuits burned. The incident became interesting and important to study. The house should have been distant with leuit so when the house caught on fire, the leuit will not burn. This is an empirical research by using interview and observation for data collection, then presented descriptively. The results showed that the position of leuit with the village is not in accordance with customary law. At first leuit was built away from the village, then the house increased in number. Finally the leuit was built in not in accordance with customary law. As a result, there was a village fire that made leuit burned down. This is a natural reaction to the non-compliance of customary rules regarding leuit distance. However, this accident is deemed as disaster rather than customary sanction.Â Keywords: food security, leuit, customary violations.